Vibration energy harvesting - Liu, Ailing. (2013)
Harvesting ambient vibration energy is an attractive method to supply power for wireless sensors or low-powered portable electronic devices. As the sources of vibration in real application often involve randomly distribution of energy over a wide frequency spectrum, the energy harvester should be designed to broaden the bandwidth and to match the resonant frequency to ambient vibration frequency for effective tapping of vibration energy. In this report, the design and testing of a non-linear piezoelectric energy harvester using a repulsive magnetic force is presented. The harmonic and random experimental tests have been carried out to study the power output response for the three types of excitation levels. In the random analysis, results have proven that the proposed nonlinear PEH is able to double the power produced by the linear one under the same random excitations. Therefore, the non-linear PEH is able to achieve higher level of harvested power and an increased bandwidth over a linear harvester. Further experiments are performed on the different distance of the two magnets to determine the optimized magnet arrangement for power optimization.